2007
DOI: 10.1177/0091270006298359
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Does Not Impair Clearance of Oral or Intravenous Midazolam, a Probe for Cytochrome P450‐3A Activity: Comparison With Grapefruit Juice

Abstract: The effect of pomegranate juice (PJ) or grapefruit juice (GFJ) on CYP3A activity was studied in vitro and in healthy human volunteers. In human liver microsomes, the mean 50% inhibitory concentrations (IC(50)) for PJ and GFJ versus CYP3A (triazolam alpha-hydroxylation) were 0.61% and 0.55%, (v/v) respectively, without preincubation of inhibitor with microsomes. After preincubation, the IC(50) for PJ increased to 0.97% (P < .05), whereas the IC(50) for GFJ decreased to 0.41% (P < .05), suggesting mechanism-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 51 publications
(161 reference statements)
8
49
0
Order By: Relevance
“…Assessment of this assumption was undertaken for drugs where i.v./oral data in the absence and presence of GFJ were reported in the same individuals. [82][83][84][85]88,154) In the case of complete intestinal inhibition, the FG of the drug in the presence of GFJ should equal 1 and this was confirmed for drugs subject solely to metabolism (e.g., midazolam, alfentanil, felodipine and nifedipine). In contrast, GFJ was unable to completely inhibit the intestinal metabolism of cyclosporine and saquinavir, suggesting biased FG estimates from GFJ data.…”
Section: In Vivo and In Vitro Methods For Estimation Of Fgmentioning
confidence: 81%
“…Assessment of this assumption was undertaken for drugs where i.v./oral data in the absence and presence of GFJ were reported in the same individuals. [82][83][84][85]88,154) In the case of complete intestinal inhibition, the FG of the drug in the presence of GFJ should equal 1 and this was confirmed for drugs subject solely to metabolism (e.g., midazolam, alfentanil, felodipine and nifedipine). In contrast, GFJ was unable to completely inhibit the intestinal metabolism of cyclosporine and saquinavir, suggesting biased FG estimates from GFJ data.…”
Section: In Vivo and In Vitro Methods For Estimation Of Fgmentioning
confidence: 81%
“…However, this approach makes several assumptions that might lead to biased estimations of intestinal availability; for example the assumption of the complete inhibition of intestinal CYP3A-mediated metabolism and that other pharmacokinetic parameters (F a , t 1/2 ) are unaltered in the presence of GFJ. An additional criterion assessed in the current analysis was that GFJ caused significant changes in the AUC of the drug investi- [38], Kharasch et al [39]. and Kupferschmidt et al [41]); bar 4 represents the weighted mean (SD) of the 3 individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of GFJ shows no effect on i.v. systemic clearance of several drugs including felodipine, midazolam, and cyclosporine [37][38][39][40][41][42] indicating an exclusive presystemic effect in the small intestine [22]. However, in certain cases the elimination half-life of drugs changes with GFJ administration [36,43,44] suggesting that exposure to a large GFJ dose may also alter systemic clearance.…”
mentioning
confidence: 99%
“…For example, pomegranate juice inhibits in vitro liver CYP3A activity (Kim et al, 2006), which suggested an effect on the metabolism of drugs that are substrates of this enzyme. However, pomegranate juice, as such a complex food, would never reach the liver, and thus far, in vivo studies have not demonstrated unequivocally that the consumption of pomegranate juice may interfere with the metabolism and clearance of some drugs (Farkas et al, 2007). There is a need to establish the actual metabolites and their concentrations in vivo as well as to investigate their effects using suitable cell models.…”
Section: Health and Ellagitannins Ellagic Acid And Their Derived Metmentioning
confidence: 99%